Prognostic biomarkers of human papilloma virus (HPV)-positive neoplasia of the upper aerodigestive tract: a systematic review - Sacks, Peta-Lee; Alvarado, Raquel; Sacks, Raymond; Gallagher, Richard; Harvey, Richard (Australian Journal of Otolaryngology; Vol 1 (June 2018): Australian Journal of Otolaryngology, 2018)
Background: HPV-positivity in oropharyngeal cancer represents a distinct biological entity in terms of underlying genetics and clinical behaviour. Next-generation sequencing has enabled researchers to identify biomarkers associated with neoplasia that may aid in predicting tumour behaviour and offer potential treatment targets. This systematic review aims to evaluate the current known prognostic biomarkers of human papilloma virus (HPV)-positive upper aerodigestive tract (UADT) neoplasia. Methods: Data sources include Embase (1947–2015), Medline (1946–2015), Cochrane Central Register of Controlled Trials, Cochrane ENT Disorders Group Trials Register and mRCT. The above sources were searched on 19th December 2015 using a comprehensive strategy for studies evaluating clinical outcomes of known prognostic biomarkers of HPV-positive UADT. Articles were limited to English language and human subjects. All studies that provided original data on the clinical implications of biomarkers in HPV-positive neoplasia were included. Outcomes relating to malignant conversion, recurrence, regional and metastatic spread as well as response to treatment were evaluated. Results: The search returned 4,702 records with thirty-one case series included in the final qualitative synthesis. These encompassed studies evaluating overall survival (n=21), disease-specific survival (n=10), recurrence (n=23), response to treatment (n=2) and risk of metastasis (n=2) with some studies evaluating more than one outcome. Overexpression of p53 and EGFR were not found to be reliable indicators of prognosis with studies demonstrating mixed results. Conclusions: It is well established that HPV-positivity correlates with improved prognosis in most UADT squamous cell carcinoma (SCC). However, there are no reliable biomarkers that can predict which tumours may fall into the more aggressive subset in this group.